2014
DOI: 10.2516/ogst/2014023
|View full text |Cite
|
Sign up to set email alerts
|

About the Use of Quality Indicators to Reduce Information Loss When Performing Upscaling

Abstract: -Hydrocarbon reservoirs are characterized by the spatial distributions of petrophysical properties. These spatial characteristics are usually derived from well data and seismic information. To study a reservoir, the engineers build a fine geological model, also called a geostatistical model, to represent the field. The purpose is to capture as well as possible the peculiarities and heterogeneity of the true reservoir. At this stage, performing a flow simulation with such detailed geological models is just too … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Preux [17] also showed that ILIv ¼ 1 when there is no information loss while ILIv ¼ 0 corresponds to a too strong upscaling process in which too much information is lost.…”
Section: Existing Error Prediction Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Preux [17] also showed that ILIv ¼ 1 when there is no information loss while ILIv ¼ 0 corresponds to a too strong upscaling process in which too much information is lost.…”
Section: Existing Error Prediction Criteriamentioning
confidence: 99%
“…In this section, the existing error prediction criteria including ILIr and ILIv information loss indices of Preux, [17] and QQ plot of Sablok and Aziz [16] will be briefly described. Preux [17] defined the data range indicator, ILIr, and the variance indicator, ILIv, as follows:…”
Section: Existing Error Prediction Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…However, selecting the most suitable technique is far from straightforward. To date, distinct criteria [2][3][4][5][6] have been proposed to quantify the information loss due to upscaling so that the quality of an upscaled model can be estimated without performing any fluid flow simulation. For instance, it was recommended to define the information loss from the ratio of the number of fine cells to the number of coarse cells or from the comparison of the histograms of the studied property at the fine and coarse scales.…”
Section: Introductionmentioning
confidence: 99%